2003
DOI: 10.1086/375070
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Physician Specialty on Counseling Practices and Medical Referral Patterns among Physicians Caring for Disadvantaged Human Immunodeficiency Virus--Infected Populations

Abstract: Data regarding the care and management of human immunodeficiency virus (HIV)-infected patients provided by infectious diseases (ID)-trained physicians, compared with data for care and management provided by other specialists, are limited. Here, we report results of a self-administered survey sent to 317 physicians (response rate, 76%) in 4 metropolitan areas of the United States who were identified as providing care to disadvantaged HIV-infected patients. ID-trained physicians who responded that they strongly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 11 publications
0
30
0
Order By: Relevance
“…In addition, other important aspects of care, including accessibility, counseling, coordination, continuity, and comprehensiveness of services, are difficult to measure from medical records. 33 In summary, in this national study of more than 5000 patients, we found that generalists with expertise in HIV infection provided a quality of care equal to that of specialists trained in infectious diseases on multiple important components of outpatient care for HIV infection. Guidelines and strategies to improve care for HIV should therefore promote the use of expert generalists as well as ID physicians.…”
Section: Commentmentioning
confidence: 66%
“…In addition, other important aspects of care, including accessibility, counseling, coordination, continuity, and comprehensiveness of services, are difficult to measure from medical records. 33 In summary, in this national study of more than 5000 patients, we found that generalists with expertise in HIV infection provided a quality of care equal to that of specialists trained in infectious diseases on multiple important components of outpatient care for HIV infection. Guidelines and strategies to improve care for HIV should therefore promote the use of expert generalists as well as ID physicians.…”
Section: Commentmentioning
confidence: 66%
“…Research shows that HIV providers (both infectious disease specialists and general medicine-certified physicians working at infectious disease clinics) are less comfortable treating hyperlipidemia, diabetes, hypertension, and depression compared to providers at general medicine clinics. 22 High-volume and/or over-paneled HIV providers also refer patients for management of these co-morbidities more often and discuss condom use and transmission risk reduction less consistently; 23 such practice patterns likely reflect multiple issues, including time constraints and competing demands, and possibly provider experience and/or comfort. Finally, data suggest that some HIV-infected patients are not receiving routine health maintenance services (e.g., mammography and colorectal cancer screening).…”
Section: Changing Providers: New Responsibilities Impending Shortagesmentioning
confidence: 99%
“…Other research suggests that infectious diseases doctors may face greater barriers to conducting prevention counseling (Duffus et al, 2003). Given recent CDC guidelines (CDC Recommendations and Reports, 2003), providers need to receive not only initial training in prevention counseling, but also have an ongoing forum to share experiences conducting prevention counseling.…”
Section: Discussionmentioning
confidence: 99%
“…This was especially true for infectious diseases specialists (Duffus et al, 2003), suggesting that HIV-care providers may experience unique barriers to HIV prevention counseling (Dawson-Rose & Myers, 2004;Mayer, Safren, & Gordon, 2004;Morin et al, 2004;Verhoeven et al, 2003). Although interventions have successfully increased the frequency of providerdelivered counseling for other health behaviors (Adams, Ockene, Wheeler, & Hurley, 1998;Boekeloo et al, 2003;Eckstrom, Hickam, Lessler, & Buchner, 1999) and for HIV risk behaviors among a general clinic population (Bluespruce et al, 2001), the components needed to increase provider-delivered prevention counseling for HIV-infected patients are not well characterized.…”
Section: Introductionmentioning
confidence: 97%